The dentition of the Early Upper Paleolithic hominins from Ksâr 'Akil, Lebanon. Issue 176 (March 2023) - Bailey, Shara E.; Tryon, Christian A.
Abstract: There are scant human remains associated with Early Upper Paleolithic (EUP) industries. The rock shelter at Ksâr 'Akil, Lebanon, is one of the few circum-Mediterranean archaeological sites with EUP artifacts and associated fossils attributed to Homo sapiens . The skull and post-crania of the juvenile 'Egbert' (Ksâr 'Akil 1) from the EUP levels (conservatively dated from ∼43 to 39 ka) have been lost; the partial edentulous maxilla of 'Ethelruda' (Ksâr 'Akil 2) from the Initial Upper Paleolithic levels has only recently been rediscovered, leaving an isolated deciduous molar (Ksâr 'Akil 3) from Levantine Aurignacian strata. A fourth individual was found adjacent to Ksâr 'Akil 1 in 1938, but never described, and is apparently also lost. New archival research at the Peabody Museum of Archaeology and Ethnography uncovered photographs and radiographs of Ksâr 'Akil 1 and photographs of the fourth individual (which we designate Ksâr 'Akil 4). These new photographs and radiographs allow a comparative dental analysis of both individuals. Radiographs confirm an age of 7–8 years for Ksâr 'Akil 1 and photographs of Ksâr 'Akil 4 suggest a similar, if not slightly younger, age. Compared to other fossil H. sapiens, the teeth of Ksâr 'Akil 1 and Ksâr 'Akil 4 are remarkably modern. The upper deciduous third premolars lack a hypocone and metacone; the upper deciduous fourth premolars of Ksâr 'Akil 1 have reduced hypocones and both individuals have upper fourth premolars and first molars with square (as opposed to skewed) occlusal outlines, resulting from a hypocone that is smaller than, or equal in size to, the metacone. The lower first permanent molars of Ksâr 'Akil 1, and possibly Ksâr 'Akil 4, are four-cusped, which is a rare trait among Paleolithic and recent H. sapiens.